On the Geomagnetic Field Line Resonance Eigenfrequency Variations during Seismic Event - Mirko Piersanti; William Jerome Burger; Vincenzo Carbone; Roberto Battiston; Roberto Iuppa; Pietro Ubertini (Remote Sensing, 2021)
In this paper, we report high statistical evidence for a seismo–ionosphere effects occurring in conjunction with an earthquake. This finding supports a lithosphere-magnetosphere coupling mechanism producing a plasma density variation along the magnetic field lines, mechanically produced by atmospheric acoustic gravity waves (AGWs) impinging the ionosphere. We have analysed a large sample of earthquakes (EQ) using ground magnetometers data: in 28 of 42 analysed case events, we detect a temporary stepwise decrease (<semantics>Δf</semantics>) of the magnetospheric field line resonance (FLR) eigenfrequency (<semantics>f*</semantics>). <semantics>Δf</semantics> decreases of ∼5–25 mHz during ∼20–35 min following the time of the EQ. We present an analytical model for <semantics>f*</semantics>, able to reproduce the behaviour observed during the EQ. Our work is in agreement with recent results confirming co-seismic direct coupling between lithosphere, ionosphere and magnetosphere opening the way to new remote sensing methods, from space/ground, of the earth seismic activity.